If the markka floated: Simulating the BOF4 model with fixed and floating exchange rates - Alpo Willman (Bank of Finland, 1988)
In this paper the BOF4 model of the Bank of Finland, which is estimated in a fi xed exchange rate - regime, i s transformed into a model with a floating exchange, rate. In endogenizing the exchange rate two al ternative assumpti ons about the formati on of exchange rate expectations are used, i.e. static and marketspecific (MS) rational expectations. We found that under static expectations the adjustment paths of the exchange rate were very volatile when shocks originated from the financial market. In response to real shocks, however, the results were not sensitive with respect to the alternative expectations formation schemes. In the case of MS-rational expectations the reactions of the exchange rate to real ,and financial shocks were, also somewha't greater than typically presented in the literature. In addition, the response paths were highly cyclical.
URN:NBN:fi:bof-201807301745
Keywords: 330